Unlocking the heterogeneity of pediatric obesity: a phenotypic subtype-based paradigm for precision management - Zhang, Yi; Zhou, Rongi; Zhang, Jiaqi; Yu, Xiaolu; Zhang, Jie (Frontiers in Endocrinology, 2026)
Childhood obesity has emerged as a major global public health crisis. Current assessment methods, primarily relying on Body Mass Index (BMI), significantly limit the effectiveness of risk stratification and treatment due to their inability to capture the notable clinical heterogeneity of this condition. To address this, this review aims to propose a conceptual framework for pediatric obesity phenotypic subtypes, transcending BMI and rooted in dominant pathophysiological mechanisms, thereby offering a new theoretical basis for understanding its heterogeneity and advancing personalized medicine. Within this framework, we categorize childhood obesity into four core subtypes: 1) the “Dysmetabolic Subtype,” characterized by insulin resistance and ectopic fat deposition; 2) the “Inflammatory Subtype,” dominated by chronic, low-grade systemic inflammation; 3) the “Neurobehavioral Subtype,” originating from central appetite and reward system dysfunction; and 4) the “Biomechanical/Structural Subtype,” primarily driven by excessive mechanical load. This paper elaborates on the biological mechanisms, clinical identification pathways, key differential diagnostic points, and associations with specific long-term disease risks for each subtype. We believe that this phenotypic subtype framework provides a clear model for interpreting the diverse clinical outcomes and disease trajectories of childhood obesity. Adopting this multidimensional, multipath paradigm is a crucial step from the “one-size-fits-all” traditional management model towards a new era of precise risk assessment and personalized, “subtype-specific” treatment, which holds significant importance for improving long-term health outcomes.